Synchrotron-based Mössbauer spectroscopy characterization of sublimated spin crossover molecules. Issue 12 (11th March 2020) - Cini, Alberto; Poggini, Lorenzo; Chumakov, Alexander I.; Rüffer, Rudolf; Spina, Gabriele; Wattiaux, Alain; Duttine, Mathieu; Gonidec, Mathieu; Fittipaldi, Maria; Rosa, Patrick; Mannini, Matteo
Abstract : The spin crossover (SCO) efficiency of [ 57 Fe(bpz)2 (phen)] molecules deposited on gold substrates was investigated by means of synchrotron Mössbauer spectroscopy. Abstract : The spin crossover (SCO) efficiency of [ 57 Fe(bpz)2 (phen)] (where bpz = bis(pyrazol-1-yl)borohydride and phen = 9, 10-phenantroline) molecules deposited on gold substrates was investigated by means of synchrotron Mössbauer spectroscopy. The spin transition was driven thermally, or light induced via the LIESST (light induced excited spin-state trapping) effect. Both sets of measurements show that, once deposited on a gold substrate, the efficiency of the SCO mechanism is modified with respect to molecules in the bulk phase. A correlation in the distribution of hyperfine parameters in the sublimated films, not evidenced so far in the bulk phase, is reported. This translates into geometrical distortions of the first coordination sphere of the iron atom that seem to correlate with the decreased spin conversion. The work reported clearly shows the potentiality of synchrotron Mössbauer spectroscopy for the characterization of nanostructured Fe-based SCO systems, thus resulting as a key tool in view of their applications in innovative nanoscale devices.